ANALISIS RASIO PROFITABILITAS SEBAGAI ALAT UKUR UNTUK MENILAI KINERJA KEUANGAN PADA PT MAYORA INDAH TBK, PERIODE 2014 – 2018 - Didik Noordiatmoko (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
This study aims to determine how the financial performance of PT Mayora Indah Tbk for 5 years, namely in 2014 to 2018. In this study the data used are the financial statements of PT Mayora Indah Tbk for 5 years. The research method used is a qualitative method, data is obtained by documentation and literature techniques. Data analysis used case study (non-hypothetical). Based on the results of research that has been carried out using the calculation of profitability ratios, namely gross profit margin, net profit margin, return on assets, and return on equity, at PT Mayora Indah Tbk. It is known that the financial performance has increased every year for the calculation of the last five years. It can be concluded that the company's financial performance at PT Mayora Indah Tbk after being calculated using these four indicators is above the industry average standard. So it can be concluded that the company's financial performance is in